2015
DOI: 10.1590/s0102-865020150110000005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the beneficial effect of sevoflurane in liver ischemia/reperfusion injury

Abstract: PURPOSE:To evaluate the underlying mechanisms by which sevoflurane protects the liver against ischemia/reperfusion injury evaluate the mechanism by which sevoflurane exerts this protective effect. METHODS:Twenty-six rats were subjected to partial ischemia/reperfusion injury for 1h: one group received no treatment, one group received sevoflurane, and sham group of animals received laparotomy only. Four hours after reperfusion, levels of alanine and aspartate aminotransferases, tumor necrosis factor-α, and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Animals showed decreased AST and ALT levels with liver preconditioning with sevoflurane for 15 min. Previously, in this laboratory, Cavalcante et al [18] showed decreased transaminase levels with continuous sevoflurane anesthesia for about 4 h of the whole experiment. In a randomized study in liver surgery, Beck-Schimmer et al [7] showed decreased AST and ALT levels in patients preconditioned with sevoflurane before liver ischemia.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Animals showed decreased AST and ALT levels with liver preconditioning with sevoflurane for 15 min. Previously, in this laboratory, Cavalcante et al [18] showed decreased transaminase levels with continuous sevoflurane anesthesia for about 4 h of the whole experiment. In a randomized study in liver surgery, Beck-Schimmer et al [7] showed decreased AST and ALT levels in patients preconditioned with sevoflurane before liver ischemia.…”
Section: Discussionmentioning
confidence: 95%
“…They also demonstrated a dose-dependent decrease in TNF- α , IL-6, and IL-10 levels. However, Cavalcante et al [18] failed to demonstrate a decrease in the cytokine levels after conditioning with sevoflurane for 4 h during the experimental liver IR. In the present study, only sevoflurane preconditioning associated to postconditioning induced lower plasma IL-6 levels, without significant changes in IL-10 and TNF- α levels.…”
Section: Discussionmentioning
confidence: 99%
“…Sun and Yang found that metformin improved the myocardial function of mice with heart failure following MI according to regulation of the expression of SIRT3 and PGC-1α in the mitochondrial inner membrane (58). However, mitochondrial dysfunction is not unique to MI; energy metabolism barriers can also occur in acute cerebral ischemia (59), renal ischemia (60), liver ischemia (61) and other ischemic diseases. This provides a novel direction in order to understand the process of MI, and further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the time required for the contrast agent to reach a peak in the liver parenchyma was shorter; the AUC was larger; and the liver parenchyma was fully developed at the peak time without an obvious dark space, illustrating that the liver microcirculation perfusion had sufficiently recovered. These results may have been due to treatment with PHT, which expanded the hepatic artery and the small branches of the artery in the liver, relieved the arterial spasm, increased liver perfusion, and improved the hepatic microcirculation …”
Section: Discussionmentioning
confidence: 99%